Endochondral ossification in vitro is influenced by mechanical bending. - Trepczik, B; Lienau, J; Schell, H; Epari, DR; Thompson, M; Hoffmann, J; Kadow-Romacker, A; Mundlos, S; Duda, G (2007)
Bone development is influenced by the local mechanical environment. Experimental evidence suggests that altered loading can change cell proliferation and differentiation in chondro- and osteogenesis during endochondral ossification. This study investigated the effects of three-point bending of murine fetal metatarsal bone anlagen in vitro on cartilage differentiation, matrix mineralization and bone collar formation. This is of special interest because endochondral ossification is also an important process in bone healing and regeneration. Metatarsal preparations of 15 mouse fetuses stage 17.5 dpc were dissected en bloc and cultured for 7 days. After 3 days in culture to allow adherence they were stimulated 4 days for 20 min twice daily by a controlled bending of approximately 1000-1500 microstrain at 1 Hz. The paraffin-embedded bone sections were analyzed using histological and histomorphometrical techniques. The stimulated group showed an elongated periosteal bone collar while the total bone length was not different from controls. The region of interest (ROI), comprising the two hypertrophic zones and the intermediate calcifying diaphyseal zone, was greater in the stimulated group. The mineralized fraction of the ROI was smaller in the stimulated group, while the absolute amount of mineralized area was not different. These results demonstrate that a new device developed to apply three-point bending to a mouse metatarsal bone culture model caused an elongation of the periosteal bone collar, but did not lead to a modification in cartilage differentiation and matrix mineralization. The results corroborate the influence of biophysical stimulation during endochondral bone development in vitro. Further experiments with an altered loading regime may lead to more pronounced effects on the process of endochondral ossification and may provide further insights into the underlying mechanisms of mechanoregulation which also play a role in bone regeneration.